Comments on "Chersine Merrem, 1820 and Chersina Gray, 1831: a nomenclatural survey by Bour & Ohler, Zootaxa, 1752: 6668" - Fritz, Uwe; Kraus, Otto (Zootaxa, 2008)
In a recent correspondence, Bour & Ohler (2008) readdress the question of whether or not Testudo hermanni Gmelin, 1789 is the type species of the genus-group names Chersine Merrem, 1820 and Medaestia Wussow, 1916 (Reptilia: Testudines: Testudinidae). The senior author, Roger Bour, co-authored the earlier description of a new genus-group name for T. hermanni (Eurotestudo Lapparent de Broin, Bour, Parham & Perälä, 2006), a name considered as an objective junior synonym of both Chersine and Medaestia by Fritz & Bininda-Emonds (2007) and Fritz & Havaš (2007), who argued that all three names are based on the same type species, T. hermanni. Bour & Ohler (2008) disputed this conclusion. In the present paper, we wish to clarify nomenclatural issues raised by Bour & Ohler (2008).